A Preliminary Study of the Efficacy of Transcranial Direct Current Stimulation in Trigeminal Neuralgia - Babakhani, Babak; Tabatabaei, Narges Hoseini; Elisevich, Kost; Sadeghbeigi, Narges; Barzegar, Mojtaba; Mobarakeh, Neda Mohammadi; Eyvazi, Fatemeh; Khazaeipour, Zahra; Taheri, Arman; Nazem-Zadeh, Mohammad-Reza (Frontiers in Human Neuroscience, 2022)
The purpose of this study is to assess the efficacy of transcranial direct current stimulation (tDCS) in patients with treatment-refractory trigeminal neuralgia (TN) and examine the utility of neuroimaging methods in identifying markers of such efficacy. Six patients with classical TN refractory to maximal medical treatment, underwent tDCS (3 cases inhibitory/cathodic and 3 cases excitatory/anodic stimulation). All patients underwent pre- and posttreatment functional magnetic resonance imaging (fMRI) during block-design tasks (i.e., Pain, Pain + tDCS, tDCS) as well as single-shell diffusion MRI (dMRI) acquisition. The precise locations of tDCS electrodes were identified by neuronavigation. Five therapeutic tDCS sessions were carried out for each patient with either anodic or cathodic applications. The Numeric Rating Scale of pain (NRS) and the Headache Disability Index (HDI) were used to score the subjective efficacy of treatment. Altered activity of regional sites was identified by fMRI and associated changes in the spinothalamocortical sensory tract (STCT) were measured by the dMRI indices of fractional anisotropy (FA) and mean diffusivity (MD). Fiber counts of the bilateral trigeminal root entry zone (REZ) were performed as an added measure of fiber loss or recovery. All patients experienced a significant reduction in pain scores with a substantial decline in HDI (P value< 0.01). Following a course of anodic tDCS, the ipsilateral caudate, globus pallidus, somatosensory cortex and the contralateral globus pallidus showed a significantly attenuated activation whereas cathodic tDCS treatment resulted in attenuation of the thalamus and globus pallidus bilaterally, and the somatosensory cortex and anterior cingulate gyrus contralaterally. dMRI analysis identified a substantial increase (>50%) in the number of contralateral sensory fibers in the STCT with either anodic or cathodic tDCS treatment in four of the six patients. A significant reduction in FA (>40%) was observed in the ipsilateral REZ in the posttreatment phase in five of the six patients. Conclusion: Preliminary evidence suggests that navigated tDCS presents a promising method for alleviating the pain of TN. Different patterns of activation manifested by anodic and cathodic stimulation require further elaboration to understand their implication. Activation and attenuation of responses at various sites may provide further avenues for condition treatment.